Facile green synthesis of bismuth sulfide radiosensitizer via biomineralization of albumin natural molecule for chemoradiation therapy aim - Hamed Nosrati; Fatemeh Abhari; Jalil Charmi; Mohammad Rahmati; Behrooz Johari; Sedigheh Azizi; Hamed Rezaeejam; Hossein Danafar (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
High atomic number Z, nanoparticles are able to enhance the photoelectric and Compton effects under X-Ray irradiation resulting the increase of radiation therapy efficacy. To achieve enhanced radiation therapy, Bi2S3 biocompatible particles coated with bovine serum albumin (BSA) (Bi2S3@BSA HNPs) were prepared through a BSA-mediated biomineralization procedure under green conditions. Then, to achieve improved chemo-radiation therapy against HT-29 cancer cells, curcumin (CUR) as natural anti-cancer therapy agent loaded on the Bi2S3@BSA (Bi2S3@BSA@CUR HNPs). Next, this synthesized nanodrug was evaluated for physical and chemical properties and in vitro cytotoxicity studies. Here, in vitro enhanced chemo-radiation combination therapy power was evaluated against HT-29 cell line under 2 Gy and 6 Gy X-ray irradiation doses. The Bi2S3@BSA HNPs without irradiation rarely affect cell viability which shown the non-toxicity of Bi2S3@BSA HNPs. The result of this study proved that Bi2S3@BSA@CUR HNPs can be used as both proficient vehicles for effective delivery of CUR and radiosensitizer in the treatment of cancer. In addition, the result of this study confirmed that the combination of high Z-element nanoradiosensitizer, Bi2S3@BSA HNPs, with a natural anti-cancer drug, CUR, enhanced therapeutic power against HT-29 cells.